Ecological Risk Assessment of Pharmaceutical Residues in Surface Water. (International Journal of Scientific Research and Management (IJSRM), 2022)
Pharmaceutical compounds have been frequently detected in the aquatic environment globally and are suspected to have some negative health consequences. The present study evaluates the sources, occurrences, spatiotemporal variabilities, concentrations, and potential risks of some pharmaceutical residues in surface water of Isolo and Amuwo Odofin areas of Lagos Nigeria. surface water samples were collected bi-monthly for a period of twenty-four months. The samples were filtered with 0.45µm glass fiber and analyzed using HPLC with a UV detector. Solid-phase extraction was achieved with OASIS HLB cartridges C18 for pre-concentration of 500ml of the sample. The target analytes were acetaminophen, ibuprofen, diclofenac, metronidazole, amoxicillin, sulfadoxin, pyrimethamin, ofloxacin, ciprofloxacin and caffeine. Levels of pharmaceutical residues (PRs) in the water samples ranged from 1.261-5.035ng / L for ibuprofen, 0.484 - 2.366ng / L for diclofenac, nd -3.57 ng / L for sulfadoxin, 0.976 -3.440 for ofloxacin, 0.585 - 0.706 ng / L for ciprofloxacin, 0.187-1.228ng / L for caffeine, 0.395-1.329 ng / L for acetaminophen and 0.032 – 0.598 ng / L for metronidazole. Amoxicillin and pyrimethamine were not detected in all the samples. The order of concentration of the pollutants are Ibuprofen > diclofenac > ofloxacin > sulfadoxin > acetaminophen> caffeine > caffeine > ciprofloxacin > metronidazole .Measured sample concentrations were compared with the approved values in “European Committee on antimicrobial susceptibility (EAUCAST)” database and some of the detected pharmaceutical compounds were found to be of high concentrations. Ecological risk assessments of each pharmaceutical active ingredient was evaluated and Rist Quotients (RQ) > 1 were found for metronidazole, ofloxacin and ciprofloxacin, indicating high risk. The need for improved wastewater treatment technologies cannot be over emphasized. Continuous monitoring and better regulatory frameworks may be necessary.